Pelatihan Pengolahan Limbah Kulit Bawang Merah menjadi Pestisida Nabati dalam Mendukung Pertanian Ramah Lingkungan di Desa Danger - Zul Hidayatullah; Nuraini Nuraini; Nur Aziza Ramdani; Masda Fadilah; Baiq Ravika Aulia Wiranti; Nuriatul Masruro (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Excessive use of chemical pesticides can have adverse effects on the environment, human health, and the sustainability of the agricultural sector. One viable solution is to utilize shallot skin waste as a botanical pesticide. This community service program aimed to enhance the knowledge and skills of Danger Village residents in processing shallot skin waste into natural pesticides to support sustainable agriculture. The methods employed included awareness-raising sessions, training, hands-on production of the botanical pesticide, and an evaluation using post-test questionnaires completed by 51 participants. The results indicated that 64.7% of participants understood the benefits of botanical pesticides, while 58.8% understood the production process. Participant satisfaction with the training was high, with an average score of 4.53 out of 5; notably, 88.2% of participants rated the training a 4 or 5. In addition to increasing participant knowledge, the activity resulted in a botanical pesticide product made from shallot skins that can serve as an alternative for natural pest control. As a follow-up measure, the service team conducted outreach across all hamlets in Danger Village to broaden the dissemination of information and encourage the continued use of botanical pesticides. This initiative demonstrates that utilizing shallot skin waste has the potential to support organic waste management and the adoption of more environmentally friendly agricultural practices.